Exploring alternative combustion control strategies for low-load exhaust gas temperature management of a heavy-duty diesel engine. (April 2019) - Guan, Wei; Zhao, Hua; Ban, Zhibo; Lin, Tiejian
The employment of aftertreatment systems in modern diesel engines has become indispensable to meet the stringent emissions regulations. However, a minimum exhaust gas temperature of approximately 200 °C must be reached to initiate the emissions control operations. Low-load engine operations usually result in relatively low exhaust gas temperature, which lead to reduced or no exhaust emissions conversion. In this context, this study investigated the use of different combustion control strategies to explore the trade-off between exhaust gas temperature, fuel efficiency, and exhaust emissions. The experiments were performed on a single-cylinder heavy-duty diesel engine at a light load of 2.2 bar indicated mean effective pressure. Strategies including the late intake valve closing timing, intake throttling, late injection timing (Tinj ), lower injection pressure (Pinj ), and internal exhaust gas recirculation and external exhaust gas recirculation were investigated. The results showed that the use of external exhaust gas recirculation and lower Pinj was not effective in increasing exhaust gas temperature. Although the use of late Tinj could result in higher exhaust gas temperature, the delayed combustion phase led to the highest fuel efficiency penalty. Intake throttling and internal exhaust gas recirculation allowed for an increase in exhaust gas temperature at the expense of higher fuel consumption. In comparison, late intake valve closure strategy achieved the best trade-off between exhaust gas temperature and net indicated specific fuel consumption, increasing the exhaust gas temperature by 52 °C and the fuel consumption penalty by 5.3% while reducing nitrogen oxide and soot emissions simultaneously. When the intake valve closing timing was delayed to after −107 crank angle degree after top dead centre, however, the combustion efficiency deteriorated and the HC and CO emissions were significantly increased. This could be overcome by combining internal exhaust gas recirculation with late intake valve closure to increase the in-cylinder combustion temperature for a more complete combustion. The results demonstrated that the 'late intake valve closure + internal exhaust gas recirculation' strategy can be the most effective means, increasing the exhaust gas temperature by 62 °C with 4.6% fuel consumption penalty. Meanwhile, maintaining high combustion efficiency as well as low HC and CO emissions of diesel engines.